Is the Xylose Test still a Worth-while Investigation?. Issue 5873 (28th July 1973) - Sladen, G. E.; Kumar, P. J.
Abstract : In a retrospective survey the results of a D-xylose absorption test have been assessed in relation to jejunal morphology and final diagnosis in 152 adult patients with various types of gastrointestinal disease. Neither urine excretion rates nor serum concentrations alone provide an adequate separation between patients with definite mucosal lesions and those without evidence of gut disease or with other types of gastrointestinal pathology. It is suggested that when a jejunal biopsy can readily be performed the xylose test serves little useful purpose in routine practice and can be positively misleading. It may still be useful as a screening test for referral for jejunal biopsy, provided that strict criteria of normality are applied.